Fear of Zina, Poor Education, and Poverty: Status of Girls in Child-Marriage in Sukabumi West Java - Dewi Candraningrum; Anita Dhewy; Andi Misbahul Pratiwi (Yayasan Jurnal Perempuan, 2016)
Indonesia is among the ten countries in the world with the highest absolute number of child brides. Indonesia is the second highest in ASEAN after Cambodia. An estimated one of five girls in Indonesia is married before they reached 18. In Indonesia girls which are prone to child marriage are: 1. Girls from rural areas as twice as likely to marry as children as those from urban areas. 2. Child brides are most likely from poor families. 3. Married girls are generally less educated, either lack of opportunity or curtailment of their schooling by early marriage. West Java and West Kalimantan are the two key provinces of origin for trafficking in Indonesia while Riau Islands and Jakarta are main destinations and transit zones. Children are trafficked for the purposes of commercial sexual exploitation, as domestic workers, child brides, and child labourers, often sent to work in hazardous environments such as on plantations and fishing platforms, while babies are trafficked for illegal adoption and organs. Another concern includes the children of illegal migrants; one study has found that when illegal migrants bring children with them, their children are at risk of abandonment, neglect, and abuse as well as trafficking. During this time, counties and cities in West Java became the biggest of supplier women migrant workers as well as girl-brides for child marriage. They came from several areas, such as Indramayu, Cirebon, Bandung, Sukabumi, and Cianjur. This research focuses at Kabupaten Sukabumi, regency in West Java where MMR and child marriage are at its highest rate presently. Method of collecting data is interviews with girls’ brides and parents as well as FGD with stakeholders at Desa Cikidang. Childmarriage at Desa Cikidang confirmed previous premises that these following causes play major roles: 1) poverty and poor access to education 2) the rise of fundamentalism leading to tabooism of sexuality and fear of zina, and finally 3) poor access to SRHR (sexual and reproductive health and rights).